Multiphoton Microscopy for the Characterization of Cellular Behavior on Naturally Derived Polysaccharide Tissue Constructs With Irregular Surfaces for the Development of Platform Biomaterials - Harling, Mitchell; Breeding, Patrick; Haysley, Travis; Chesley, Mitchell; Mason, Michael; Tilbury, Karissa (Frontiers in Bioengineering and Biotechnology, 2020)
Over the past decade, the use of polymers as platform materials for biomedical applications including tissue engineering has been of rising interest. Recently, the use of naturally derived polysaccharides as 3-D scaffolds for tissue regeneration has shown promising material characteristics; however, due to complexities in composition, morphology, and optical properties, adequate spatial and temporal characterization of cellular behavior in these materials is lacking. Multiphoton microscopy has emerged as a viable tool for performing such quantification by permitting greater imaging depth while simultaneously minimizing un-favorable scattering and producing high-resolution optical cross sections for non-invasive analysis. Here we describe a method using endogenous contrast of nanocellulose fibers (CNF) using Second Harmonic Generation (SHG), combined with 2-photon fluorescence of Cell Tracker Orange (CTO) for spatial and longitudinal imaging of cellular proliferation. CTO is an ideal fluorophore to avoid the broad CNF autofluorescence allowing for segmentation of cells using a semi-automatic routine. Individual cells were identified using centroid locations for 3D cell proliferation. Overall, the methods presented are viable for investigation of cellular interactions with polysaccharide candidate biomaterials.